-9y+20=-2(y-3)

Simple and best practice solution for -9y+20=-2(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9y+20=-2(y-3) equation:



-9y+20=-2(y-3)
We move all terms to the left:
-9y+20-(-2(y-3))=0
We calculate terms in parentheses: -(-2(y-3)), so:
-2(y-3)
We multiply parentheses
-2y+6
Back to the equation:
-(-2y+6)
We get rid of parentheses
-9y+2y-6+20=0
We add all the numbers together, and all the variables
-7y+14=0
We move all terms containing y to the left, all other terms to the right
-7y=-14
y=-14/-7
y=+2

You can always share this solution

See similar equations:

| 5(x+2)=6x+3x-14 | | -3(y+4)=5y-28 | | 10k(k+2)=k-6 | | -45b=-39b | | d+12/6=20/8 | | F(t)=1,500(1.045) | | j*7=56 | | v*7=28 | | 7*v=48 | | v*7=48 | | 2*i=18 | | c*5=35 | | 4a+a=20;a= | | 1/4-10=7;b= | | 1/3(x+8)=10 | | 2x+25=32 | | 7w-38=-4(w-7) | | v2=-84 | | 4(v+4)=-8v+40 | | 7z-9=-3 | | -3y-9=2y=3 | | y=3=4y-18 | | 31=5(y+8)+4y | | 30=6v+3(v-5) | | 4(w+8)+4w=16 | | x-(x*0.08)=3270191.37 | | x-(x*0.08)=896023.87 | | 2^(x-2)-11^(-10x)=0 | | 6w+7(w+3)=-31 | | -3=5(y-7)+3y | | 6(n+7)=2(21+3) |

Equations solver categories